Is public health concern a sufficient reason to illegalize consensual incest?. (3rd March 2023) - Campo Redondo, Maria; Andrade, Gabriel
Abstract: Incest taboos are universal, but it is questionable whether consensual incest should continue to be illegal. The most common argument in favor of the illegalization of consensual incest appeals to genetic risks and the harm to potential offspring. In this article, we examine whether public health concern is a sufficient reason to illegalize consensual incest. We posit that indeed, incest represents a risk, but this is not reason enough to illegalize incest. For, other circumstances of sexual intercourse may lead to similar risks, and yet, such practices are not illegal. While those practices may represent an added risk to public health, to forbid them as a way to improve the genetic pool would be akin to eugenic program, and that is morally objectionable. This does not imply that consensual incest ought to be legal, for there may be other good reasons to illegalize it. But they do not relate to public health and genetic risks, and consequently, medical practitioners and public health officials ought to avoid using their medical authority as a platform to make moral pronouncements.